Deriving Economic Potential and GHG Emissions of Steel Mill Gas for Chemical Industry - Collis, Jason; Strunge, Till; Steubing, Bernhard; Zimmermann, Arno; Schomäcker, Reinhard (Frontiers in Energy Research, 2021)
To combat global warming, industry needs to find ways to reduce its carbon footprint. One way this can be done is by re-use of industrial flue gases to produce value-added chemicals. Prime example feedstocks for the chemical industry are the three flue gases produced during conventional steel production: blast furnace gas (BFG), basic oxygen furnace gas (BOFG), and coke oven gas (COG), due to their relatively high CO, CO2, or H2 content, allowing the production of carbon-based chemicals such as methanol or polymers. It is essential to know for decision-makers if using steel mill gas as a feedstock is more economically favorable and offers a lower global warming impact than benchmark CO and H2. Also, crucial information is which of the three steel mill gases is the most favorable and under what conditions. This study presents a method for the estimation of the economic value and global warming impact of steel mill gases, depending on the amount of steel mill gas being utilized by the steel production plant for different purposes at a given time and the economic cost and greenhouse gas (GHG) emissions required to replace these usages. Furthermore, this paper investigates storage solutions for steel mill gas. Replacement cost per tonne of CO is found to be less than the benchmark for both BFG (50-70 €/tonne) and BOFG (100-130 €/tonne), and replacement cost per tonne of H2 (1800-2100 €/tonne) is slightly less than the benchmark for COG. Of the three kinds of steel mill gas, blast furnace gas is found to be the most economically favorable while also requiring the least emissions to replace per tonne of CO and CO2. The GHG emissions replacement required to use BFG (0.43-0.55 tonnes-CO2-eq./tonne CO) is less than for conventional processes to produce CO and CO2, and therefore BFG, in particular, is a potentially desirable chemical feedstock. The method used by this model could also easily be used to determine the value of flue gases from other industrial plants.